THE WHITE HOUSE: Office of the Press Secretary -- Press Briefing by Dr. Neal Lane, Director of The President's Office on Science and Technology Policy and Dr. Francis Collins, Director of the Human Genome Project (M2 Presswire, 2000)
As you know, President Clinton and U.K. Prime Minister Blair announced their support today for making the raw, fundamental human DNA sequence information freely available to scientists around the world in order to stimulate the rapid development of genome-based health care products. Supporters for the Human Genome Project have long held that open access to such information will speed up the translation of that basic data into therapies that can cure or prevent disease rather than simply treating symptoms, as well as unlocking the mysteries of normal human development. DR. LANE: As I said earlier, this statement really in no way is intended to change patent policy, or changes patent policy. I'm sure you know the Patent Trade Office has recently issued guidelines on how they would deal with requests for patents on genetic material. And it's clear that they require a certain level of utility. This statement does not address that set of issues at all. I think the patent policies and patent decisions are up to that office, and what this statement emphasizes is the importance of making available the raw, fundamental human genome data that I think no one disputes is not subject to patent. DR. LANE: I think you would have to direct your question to the Patent Office. But what I think is clear is that everybody agrees that the raw, fundamental sequence data of the human genome is not patentable. I think discussions have to do with what level of utility does one need to demonstrate in order for that information to be patented. And I think the specifics of that, you would need to address to the Patent Office.